PERAN KOMPENSASI DAN PENGEMBANGAN KARIR SEBAGAI UPAYA PENINGKATAN PRESTASI KERJA (Studi Pada Pada Karyawan Bank Jatim Cabang Sumenep) - Yuda Imawan Sutanto; Fatimah Riswati, Fatimah Riswati; Chamariyah Chamariyah (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2021)
This research was conducted at Sumenep Jatim Bank, with a total sample of 57 people. The purpose of this study are: 1) To find out the description of compensation, Career Development, and employee work performance at Bank Jatim, Sumenep Branch; 2) To test and analyze the effect of compensation, and career development of partial on employee work performance at Bank Jatim, Sumenep Branch; 3) To test and analyze the effect of compensation, career development and competency of simultaneously on the work performance of employees at Bank Jatim, Sumenep Branch. Data analysis using SPSS, this type of research is explanatory research using quantitative research approaches. The results showed that: 1 Partially, Compensation and Career Development had a significant influence on the Job Performance of Bank Jatim, Sumenep Branch. So in this case the hypothesis is accepted and proven true; 2) Partially, compensation, and career development have a significant influence on the work performance of Bank Jatim, Sumenep Branch. So in this case the hypothesis is accepted and proven true